Kajian Siklus Daur Hidup pada Proses Produksi Industri Stainless Steel Gresik - Enrico Gianpratama Latuhihin; Tuhu Agung Rachmanto (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
“Gresik Stainless Steel Industry is one of the largest stainless steel factories in Indonesia since 1996 until now. With a sufficiently large production capacity, it is possible for the production process to produce emissions/by-products that can pollute the environment. This study approaches the production process of the Gresik Stainless Steel Industry using the Life Cycle Assessment (LCA) method. The scope of this research is gate to gate or during the stainless steel production process from the entry of materials to the release of finished products which include operating units from Coil Preparation Line Units, Coil Grinding Line Units, Mill Units, Annealing Pickling Line Units, Skinpass Units, Slitter Units , to Cut-To-Length Units. Life cycle assessment is carried out using the midpoint approach of the TRACI 2.1 method. Based on the results of the analysis, the APL unit is the operating unit that has the greatest influence on the eutrophication impact which has a total normalized value of 5025.309. This is due to the use of nitric acid as the main ingredient in the acidification process for the stainless steel production process.”